2016
DOI: 10.1016/j.gca.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Potential origin and formation for molecular components of humic acids in soils

Abstract: Soil humic acids are the base soluble/acid insoluble organic components of soil organic matter. Most of what we know about humic acids comes from studies of their bulk molecular properties or analysis of individual fractions after extraction from soils. This work attempts to better define humic acids and explain similarities and differences for several soils varying in degrees of humification using advanced molecular level techniques. Our investigation using electrospray ionization coupled to Fourier transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 52 publications
3
86
0
4
Order By: Relevance
“…Other non-pyrogenic OM sources of condensed aromatic OM are abundant in the geosphere, including woody peat, coal, kerogen, and oil (Yoshioka and Ishiwatari, 2005;Hammes et al, 2007;Wang et al, 2012;Hartman et al, 2015;Li et al, 2017). Still other studies have found that nonpyrogenic OM can be readily transformed to condensed aromatic OM, which would appear to be pyrogenic, through photolytic, microbial, or chemical degradative processes (Glaser and Knorr, 2008;Chen et al, 2014;Waggoner et al, 2015;DiDonato et al, 2016).…”
Section: Methodology/conceptual Issuesmentioning
confidence: 99%
“…Other non-pyrogenic OM sources of condensed aromatic OM are abundant in the geosphere, including woody peat, coal, kerogen, and oil (Yoshioka and Ishiwatari, 2005;Hammes et al, 2007;Wang et al, 2012;Hartman et al, 2015;Li et al, 2017). Still other studies have found that nonpyrogenic OM can be readily transformed to condensed aromatic OM, which would appear to be pyrogenic, through photolytic, microbial, or chemical degradative processes (Glaser and Knorr, 2008;Chen et al, 2014;Waggoner et al, 2015;DiDonato et al, 2016).…”
Section: Methodology/conceptual Issuesmentioning
confidence: 99%
“…Although based on electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry (ESI-FTICRMS) data, it was shown that carboxylic acids bound to both aliphatic and condensed aromatic molecules are common components of HAs (DiDonato and Hatcher 2016;DiDonato et al 2016). In their opinion, the vicinities of a variety of carboxylic groups to an assortment of structural components would indicate that Blignin-like^compounds resent the third major molecular group common to HAs (DiDonato et al 2016).…”
Section: Stability Of Organic Matter In Soilsmentioning
confidence: 99%
“…Humic substances (HSs) composed of humic and fulvic acids are produced via the decay of plants rich in lignin (Di Donato et al ., ), forming supramolecular associations of heterogeneous molecules held together by hydrophobic interactions (Nebbioso & Piccolo, ). According to Di Donato et al .…”
Section: Introductionmentioning
confidence: 99%
“…According to Di Donato et al . (), HSs can be classified into the following molecular groups based on the Van Krevelen () diagram: lignin‐like molecules, carboxyl‐containing aliphatic molecules and condensed aromatic molecules related to black carbon.…”
Section: Introductionmentioning
confidence: 99%